An Analysis of the Influence of Workload, Compensation, and Work Environment on the Job Satisfaction of Health Workers at Hermina Hospital, Cilegon - Akemah, Alden Jiraldi; Alifia, Jihan Fasya; Ginanjar, Muhammad Raihan; Namira, Syafira Nihla; Bernarto, Innocentius (Dinasti International Journal of Education Management and Social Science, 2025)
Job satisfaction is a crucial factor in maintaining workforce performance and sustainability. Various changes in compensation systems, work environment conditions, and workload require a more in-depth analysis of the influence of these three aspects on job satisfaction. This study was conducted to identify the key determinants of job satisfaction as a basis for strengthening human resource management policies. The study aims to analyse the influence of workload, compensation, and the work environment on job satisfaction among healthcare workers. The study used SEMPLS with 200 respondents. The results of the study indicated that Compensation, Work Environment, and Workload had a positive and significant effect on Job Satisfaction. Among these variables, compensation emerges as the strongest predictor, followed by the work environment, whereas workload shows a smaller yet still significant effect. The study model also shows that these three variables are able to explain most of the variation in Job Satisfaction, with good validity, reliability, and predictive relevance. These findings confirm that employee job satisfaction is strongly influenced by fair compensation systems, supportive work environments, and well-regulated workload management.